Environmental Accounting Disclosure, Green Process Innovation, and Environmental Management Accounting Improving Economic Performance - Cahyaningsih Cahyaningsih; Fadilah Usyulia Ihromi (Postgraduate Program Merdeka University, 2024)
This study examines the effect of environmental accounting disclosure, green process innovation, and environmental management accounting on economic performance. This study analyzes 22 basic material sector companies listed on the Indonesia Stock Exchange in 2017-2021. Data were analyzed using panel data regression, with the selected model being the fixed effect model. The result indicates that environmental accounting disclosure, green process innovation, and environmental management accounting positively affect economic performance. Companies that carry out environmental accounting disclosures can reduce the negative impact of the company's operational activities to improve the company's economic performance. Companies that are increasingly innovative in their production processes can save energy and make production costs efficient to improve their economic performance. Companies that can implement environmentally friendly programs mean they can support long-term strategies that have an impact on improving the company's economyDOI: https://doi.org/10.26905/afr.v7i1.10840